Sub-Saharan Africa and G20 Responses to the Global Financial Crises: First, do not harm - Andreas Freytag; Peter Draper; Matthias Bauer (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2011)
These days, plenty of cognoscenti in academia and politics share the common concern that the build-up of global macroeconomic imbalances threatens the international economy. While there is broad disagreement on the essence of what an imbalance exactly is, the term is generally associated with perceived macroeconomic disequilibria in balance of payments, but also fiscal and monetary policy. In the aftermath of the financial crisis the G20 leaders addressed these issues in the 'Seoul Action Plan' adopted in November 2010. The G20 emphasizes the need for domestic policies directed to increase savings in the deficit countries and to increase absorption in the surplus countries. In this paper we assess the G20's desire, mostly on paper, in the light of its implications for sub-Saharan Africa. We first review how sub-Saharan Africa was hit by the crisis and consider prevailing crisis responses. We then assess whether the G20 is on the right track and whether the G20 is the appropriate 'coordination' body to solve the dissonance problem of national economic policies. We conclude that there could be a potential positive impact of the 'Seoul Consensus' on Africa, if the rich countries really abstain from trade protection measures and currency wars.
urn:nbn:de:gbv:27-20131118-111402-1
Keywords: 330; Sub-saharan Africa; Trade; Macro-Coordination; G 20; Crisis Response; Finanzkrise; Makroökonomischer Einfluss; Internationale Wirtschaftspolitik; Handelsliberalisierung; G20-Staaten; Entwicklungsländer